Prevalence of Helicobacter pylori in patients with peptic ulcer disease - Uppin, Mrutyunjay I.; Hannurkar, Kapildev K. (International Surgery Journal, 2018)
Background: Prevalence of Helicobacter pylori (H. pylori) emerges throughout the world and instigates peptic ulcer disease (PUD). The study was conducted with the aim to determine the prevalence of H. pylori in patients with PUD undergoing upper gastrointestinal endoscopy. Methods: This prospective study was conducted on 150 cases of PUD from August 2009 to February 2011. Endoscopy was done in all cases. Biopsy was done and sent for histopathological examination and rapid urease test for confirmation of presence of H. pylori. Results: Out of 150 patients with mean age of 45.76 years, 109 patients were diagnosed to have been infected with Helicobacter pylori (72.66%). Out of 89 patients with gastric ulcer, 61 patients were infected with Helicobacter pylori (68.53%). Forty two out of 51 patients (82.35%) with duodenal ulcers and 06 of 10 patients (60%) with carcinoma of stomach were positive for H. pylori. The remaining patients were found to be negative for the H. pylori infection. Conclusions: The findings of the study conclude that H. pylori was consistently associated with PUD.